Sociological perspective of performance appraisal: an overview - Yusof, Ab. Aziz; Ali, Juhary (Sekolah Pengurusan, Universiti Utara Malaysia, 2000)
In today's competitive global market, managing employees is becoming more challenging and complex. There is a great demand for an effective managerial style as employees' expectations towards work are more diversified than before, It requires managers to acquire better knowledge and skills in understanding employees behavior at work. As employees are the key players in an organization, they play a vital role in determining the success and the survival of the organization. Employees can accept or reject any rule, procedure and regulation in the organization. Managers should understand that when employees come to work, they are not only contributing their knowledge, skills and abilities but also their emotions, creativity and personalities. So, in appraising their performance all the above factors should be taken into consideration because they affect employees' overall performance. Furthermore, the workers who come to work do not only aim for recognition and rewards but also for status, social acceptance, and power. Thus, every employee from all hierarchies will put great concern and interest on performance appraisal issues as they influence his/her future career development in the organization. Employees have realized that the outcomes of performance appraisal affect their rewards, determine their future career and give an impact on social relationships among them. Besides, the performance appraisal acts as one of the determinant factors in work motivation, commitment and loyalty. To ensure the success of performance appraisal, a new approach in evaluating employees that is totally different from evaluating other factors of production is needed. This paper highlights performance appraisal issues and determines how far the contributions of performance appraisal are being recognized, valued, and respected by the organization.